Two Nice Determinantal Expressions and A Recurrence Relation for the Apostol–Bernoulli Polynomials - Qi, Feng; Guo, Bai-Ni (IndoMS, 2017)
In the paper, the authors establish two nice determinantal expressions and a recurrence relation for the Apostol–Bernoulli polynomials.